Long gas barrier laminate and manufacturing method thereof
Patent Information
- Application Number
- JP2021079138
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2014-03-31
- Filing Date
- 2021-05-07
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2035-03-27
AI Technical Summary
【0010】 本発明によれば、ロール状に巻き取る際やロールから繰り出す際の作業性に優れる長尺のガスバリア性積層体とその製造方法が提供される。
Smart Images

Figure 0007641811000001 
Figure 0007641811000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a long gas barrier laminate which is excellent in workability when wound into a roll or when unwound from the roll, and to a method for producing the same. [Background technology]
[0002] In recent years, in order to realize thinner, lighter, more flexible displays such as liquid crystal displays and electroluminescence (EL) displays, so-called gas barrier films, which are formed by laminating a gas barrier layer on a transparent plastic film, have been used in place of glass plates.
[0003] In gas barrier films, it has been proposed to provide a smoothing layer on the substrate in order to fill in irregularities on the substrate surface and improve interlayer adhesion. For example, Patent Document 1 describes a transparent gas barrier film in which at least one surface smooth layer and at least one inorganic barrier layer are laminated on a transparent plastic substrate, and the arithmetic mean roughness of the surface smooth layer etc. is specified.
[0004] When gas barrier films are produced industrially, the roll-to-roll method is usually used. For example, Patent Document 2 describes a method for producing a gas barrier film, which comprises winding up a resin film having smooth layers (surface smoothing layers) on both sides, with the hardness of the smooth layer surfaces on both sides specified, into a roll, and then providing a gas barrier layer while unwinding the resin film. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2003-154596 A [Patent Document 2] International Publication No. 2010 / 026852 Summary of the Invention [Problem to be solved by the invention]
[0006] As described above, it is known that the interlayer adhesion is improved by providing a smoothing layer in a gas barrier film, and as a result, the gas barrier properties and the like of the gas barrier film are improved. However, when such gas barrier films are manufactured using the roll-to-roll method, problems such as blocking (films sticking to each other) and air entrapment (wrinkles) can occur when the film is wound into a roll or unwound from the roll.
[0007] The present invention has been made in consideration of the above-mentioned circumstances, and has an object to provide a long gas barrier laminate which is easy to work with when wound into a roll or when unrolled from the roll, and a method for producing the same. [Means for solving the problem]
[0008]
[0011] As a result of intensive investigations to solve the above-mentioned problems, the present inventors have discovered that a long gas barrier laminate comprising a functional layer laminated on one side of a substrate, and a smoothing layer and a gas barrier layer laminated in this order on the other side of the substrate, in which the static friction coefficient between the side of the functional layer opposite the substrate and the side of the gas barrier layer opposite the substrate falls within a specific range, has excellent workability when wound into a roll or unrolled from the roll, which led to the completion of the present invention.
[0009] Thus, according to the present invention, there are provided the following gas barrier laminates (1) to (7) and (8): 、 (9) A method for producing a gas barrier laminate is provided. (1) A long gas barrier laminate comprising a functional layer laminated on one surface of a substrate, and a smoothing layer and a gas barrier layer laminated in this order on the other surface of the substrate, The arithmetic mean roughness (Ra) of the surface of the functional layer opposite to the substrate side is 5 to 14.7 nm, and the maximum cross-sectional height (Rt) of the roughness curve is 100 to 1000 nm, A long gas barrier laminate, characterized in that the static friction coefficient between the surface of the functional layer opposite the substrate side and the surface of the gas barrier layer opposite the substrate side is 0.35 to 0.80. (2) A long gas barrier laminate according to (1), wherein the surface of the gas barrier layer opposite the substrate has an arithmetic mean roughness (Ra) of 5 nm or less and a maximum cross-sectional height (Rt) of the roughness curve of 100 nm or less. (3) A long gas barrier laminate according to (1), in which the static friction coefficient between the surface of the functional layer opposite the substrate and the surface of the smoothing layer opposite the substrate is 0.35 to 0.80. (4) A long gas barrier laminate according to (1), wherein the smoothing layer has an arithmetic mean roughness (Ra) of 5 nm or less and a maximum cross-sectional height (Rt) of a roughness curve of the surface opposite to the substrate. (5) The long gas barrier laminate according to (1), wherein the functional layer is a hard coat layer made of a cured product of an active energy ray-curable resin composition. (6) The long gas barrier laminate according to (1), wherein the smoothing layer is made of a cured product of an active energy ray-curable resin composition. (7) The long gas barrier laminate according to (1), wherein the gas barrier layer is a layer obtained by modifying a layer containing a polysilazane compound. (8) A method for producing the long gas barrier laminate according to claim 1, comprising the steps of: A step (aI) of forming a smoothing layer on a substrate resin film while transporting the substrate resin film in a certain direction, and then winding up the obtained resin film with the smoothing layer into a roll; The resin film with the smoothing layer obtained in step (aI) is continuously unwound from the roll and transported in a certain direction, while the resin film with the smoothing layer is subjected to the following on the resin film surface: The arithmetic mean roughness (Ra) of the surface opposite to the substrate is 5 to 14.7 nm, and the maximum cross-sectional height (Rt) of the roughness curve is 100 to 1000 nm. After forming the functional layer, a step (a-II) of winding up the obtained resin film with the functional layer and the smoothing layer into a roll; and a step (a-III) of continuously unwinding the resin film from the roll of the resin film with the functional layer and the smoothing layer obtained in step (a-II) and transporting the resin film in a constant direction, and then forming a gas barrier layer having a static friction coefficient with the functional layer of 0.35 to 0.80 on the surface of the smoothing layer of the resin film with the functional layer and the smoothing layer, and then winding up the resulting gas barrier laminate into a roll; The method for producing a long gas barrier laminate, comprising the steps of: (9) A method for producing the long gas barrier laminate according to (1), comprising the steps of: While transporting the base resin film in a certain direction, The arithmetic mean roughness (Ra) of the surface opposite to the substrate is 5 to 14.7 nm, and the maximum cross-sectional height (Rt) of the roughness curve is 100 to 1000 nm. After forming the functional layer, a step (bI) of winding up the obtained resin film with the functional layer into a roll; A step (b-II) of continuously unwinding the resin film from the roll of the functional layer-attached resin film obtained in step (bI) and transporting the resin film in a constant direction while forming a smoothing layer on the resin film surface of the functional layer-attached resin film, and then winding up the obtained functional layer and smoothing layer-attached resin film into a roll; and a step (b-III) of continuously unwinding the resin film from the roll-shaped functional layer and smoothing layer-attached resin film obtained in step (b-II) and transporting the resin film in a constant direction while forming a gas barrier layer having a static friction coefficient with the functional layer of 0.35 to 0.80 on the surface of the smoothing layer of the functional layer and smoothing layer-attached resin film, and then winding up the resulting gas barrier laminate into a roll; The method for producing a long gas barrier laminate, comprising the steps of: Effect of the Invention
[0010] According to the present invention, there are provided a long gas barrier laminate which is excellent in workability when wound into a roll and when unwound from the roll, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below, divided into the sections of 1) a long gas barrier laminate and 2) a method for producing a long gas barrier laminate.
[0012] 1) Long gas barrier laminate The long gas barrier laminate of the present invention is a long gas barrier laminate comprising a functional layer laminated on one side of a substrate, and a smoothing layer and a gas barrier layer laminated in this order on the other side of the substrate, and is characterized in that the static friction coefficient between the side of the functional layer opposite the substrate and the side of the gas barrier layer opposite the substrate is 0.35 to 0.80.
[0013] (1) Base material The substrate constituting the gas barrier laminate of the present invention is not particularly limited as long as it can support the functional layer, the smoothing layer and the gas barrier layer and is in the form of a long sheet or film. In the present invention, the term "long" means that the shape is a strip whose longitudinal direction is longer than its width direction (preferably 10 times or more longer). In the following description, the term "long" may be omitted.
[0014] The length (length in the longitudinal direction) of the substrate is not particularly limited, but is usually 400 to 2000 m. The width (length in the width direction) of the substrate is not particularly limited, but is usually 450 to 1300 mm, preferably 530 to 1280 mm. The thickness of the substrate is not particularly limited, but is usually 1 to 60 μm, preferably 5 to 50 μm, more preferably 10 to 30 μm.
[0015] The substrate may be a resin film, and examples of the resin component of the resin film include polyimide, polyamide, polyamideimide, polyphenylene ether, polyether ketone, polyether ether ketone, polyolefin, polyester, polycarbonate, polysulfone, polyether sulfone, polyphenylene sulfide, acrylic resin, cycloolefin polymer, and aromatic polymer. These resin components may be used alone or in combination of two or more.
[0016] Among these, polyester, polyamide, polysulfone, polyethersulfone, polyphenylene sulfide or cycloolefin polymers are more preferred, and polyester or cycloolefin polymers are even more preferred, because of their excellent transparency and versatility.
[0017] Examples of the polyester include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polyarylate.
[0018] Examples of the cycloolefin polymer include norbornene polymers, monocyclic olefin polymers, cyclic conjugated diene polymers, vinyl alicyclic hydrocarbon polymers, and hydrogenated products thereof.
[0019] The resin film may contain various additives as long as the effects of the present invention are not impaired. Examples of additives include ultraviolet absorbers, antistatic agents, stabilizers, antioxidants, plasticizers, lubricants, fillers, coloring pigments, etc. The content of these additives may be appropriately determined according to the purpose.
[0020] The resin film can be obtained by preparing a resin composition containing predetermined components and molding it into a film. The molding method is not particularly limited, and known methods such as a casting method and a melt extrusion method can be used.
[0021] (2) Functional layer Examples of the functional layer constituting the gas barrier laminate of the present invention include a hard coat layer, an antiglare hard coat layer, and an antistatic layer, each of which has a function of surface protection, antiglare and surface protection, or antistatic and surface protection. The functional layer may also be an ultraviolet absorbing layer, an infrared absorbing layer, a primer layer, etc. The hard coat layer preferably has a pencil hardness of at least H. If the pencil hardness is at least H, sufficient scratch resistance can be provided. The surface resistivity of the antistatic layer is 1×10 4 ~1×10 11It is preferable to set the value within the range of Ω / □. Furthermore, by providing a functional layer, friction between the functional layer and the smoothing layer and between the functional layer and the gas barrier layer is made appropriate, so that the resulting gas barrier laminate has excellent workability when wound into a roll and when unrolled from the roll.
[0022] An example of the hard coat layer is a layer made of a cured product of an active energy ray-curable resin composition. The active energy ray-curable resin composition is a composition that contains a polymerizable compound and can be cured by irradiation with active energy rays. The polymerizable compound may, for example, be a polymerizable prepolymer or a polymerizable monomer. Examples of the polymerizable prepolymer include polyester acrylate prepolymers obtained by reacting a polyester oligomer having hydroxyl groups at both ends with (meth)acrylic acid, epoxy acrylate prepolymers obtained by reacting a low molecular weight bisphenol type epoxy resin or novolac type epoxy resin with (meth)acrylic acid, urethane acrylate prepolymers obtained by reacting a polyurethane oligomer with (meth)acrylic acid, and polyol acrylate prepolymers obtained by reacting a polyether polyol with (meth)acrylic acid.
[0023] Examples of the polymerizable monomer include bifunctional (meth)acrylates such as 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, caprolactone-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified phosphoric acid di(meth)acrylate, allylated cyclohexyl di(meth)acrylate, and isocyanurate di(meth)acrylate; trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propionic acid-modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and propylene oxide-modified trimethylolpropane tri(meth)acrylate. trifunctional (meth)acrylates such as dipentaerythritol penta(meth)acrylate modified with propionic acid, dipentaerythritol hexa(meth)acrylate modified with caprolactone, and the like; and vinyl compounds such as ethylene glycol divinyl ether, pentaerythritol divinyl ether, 1,6-hexanediol divinyl ether, trimethylolpropane divinyl ether, ethylene oxide modified hydroquinone divinyl ether, ethylene oxide modified bisphenol A divinyl ether, pentaerythritol trivinyl ether, dipentaerythritol hexavinyl ether, ditrimethylolpropane polyvinyl ether, but are not necessarily limited thereto. These polymerizable compounds may be used alone or in combination of two or more. Here, the expression "(meth)acryloyl group" is meant to include both an acryloyl group and a methacryloyl group.
[0024] The active energy ray-curable resin composition may contain a polymeric resin component that does not have reaction curability by itself, such as an acrylic resin. The viscosity of the composition can be adjusted by adding the polymeric resin component.
[0025] Examples of active energy rays include ultraviolet rays, electron beams, α rays, β rays, γ rays, etc. Among these, ultraviolet rays are preferred as active energy rays because they can be generated using a relatively simple device.
[0026] When ultraviolet rays are used as the active energy rays, the active energy ray-curable resin composition (that is, the ultraviolet ray-curable resin composition) preferably contains a photopolymerization initiator.
[0027] The photopolymerization initiator is not particularly limited as long as it initiates a polymerization reaction by irradiation with ultraviolet light. Examples of the photopolymerization initiator include benzoin-based polymerization initiators such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin-n-butyl ether, and benzoin isobutyl ether; acetophenone, 4'-dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxyphenyl)phenyl]-2-propan-1-one, and the like. acetophenone-based polymerization initiators such as {(2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one; benzophenone-based polymerization initiators such as benzophenone, 4-phenylbenzophenone, 4,4'-diethylaminobenzophenone, and 4,4'-dichlorobenzophenone; anthraquinone-based polymerization initiators such as 2-methylanthraquinone, 2-ethylanthraquinone, 2-t-butylanthraquinone, and 2-aminoanthraquinone; thioxanthone-based polymerization initiators such as 2-methylthioxanthone, 2-ethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, and 2,4-diethylthioxanthone; and the like. The content of the photopolymerization initiator is not particularly limited, but is usually from 0.2 to 30% by mass, and preferably from 0.5 to 20% by mass, based on the polymerizable compound.
[0028] The active energy ray curable resin composition preferably contains fine particles such as organic fine particles, inorganic fine particles, etc. By using an active energy ray curable resin composition containing fine particles, the surface roughness and antiglare property of the hard coat layer can be efficiently controlled.
[0029] Examples of organic fine particles include fine particles made of polystyrene resin, styrene-acrylic copolymer resin, acrylic resin, amino resin, divinylbenzene resin, silicone resin, urethane resin, melamine resin, urea resin, phenol resin, benzoguanamine resin, xylene resin, polycarbonate resin, polyethylene resin, polyvinyl chloride resin, etc. Among these, silicone fine particles made of silicone resin are preferred.
[0030] Examples of inorganic fine particles include silica particles, metal oxide particles, and alkyl silicate particles. Examples of the silica particles include colloidal silica and hollow silica. Examples of the metal oxide particles include particles of titanium oxide, zinc oxide, zirconium oxide, tantalum oxide, indium oxide, hafnium oxide, tin oxide, and niobium oxide. The alkyl silicate particles may be those having the formula: R a -O〔-{Si(OR b )2}-O-〕 n -R a (In the formula, R a and R b represents an alkyl group having 1 to 10 carbon atoms, and n represents an integer of 1 or more. Among these, silica particles or alkyl silicate particles are preferred because they have excellent compatibility with the curable component and can efficiently control the refractive index of the optical adjustment layer. These fine particles can be used alone or in combination of two or more kinds.
[0031] The shape of the fine particles is not particularly limited, and fine particles of various shapes, such as amorphous and spherical, can be used. The average particle size of the fine particles is usually 0.001 to 10 μm, and preferably 0.005 to 5 μm. The average particle size of the fine particles can be measured by a laser diffraction / scattering method.
[0032] When the active energy ray-curable resin composition contains fine particles, the content of the fine particles is preferably from 0.1 to 170 mass %, more preferably from 1 to 50 mass %, based on the solid content of the resin composition.
[0033] The active energy ray-curable resin composition preferably contains a leveling agent. By using an active energy ray-curable resin composition containing a leveling agent, the surface roughness of the hard coat layer can be efficiently controlled. The leveling agent may be a siloxane-based compound, and among these, a compound having a dialkylsiloxane skeleton, such as polydimethylsiloxane and its derivatives, is preferred. When the active energy ray-curable resin composition contains a leveling agent, the content of the leveling agent is preferably from 0.01 to 10 mass %, more preferably from 0.05 to 5 mass %, based on the solid content of the resin composition.
[0034] The active energy ray-curable resin composition may contain other components as long as the effects of the present invention are not impaired. Examples of other components include antistatic agents, stabilizers, antioxidants, plasticizers, lubricants, coloring pigments, etc. The content of these may be appropriately determined depending on the purpose.
[0035] The method of forming the hard coat layer is not particularly limited. For example, a coating liquid containing an active energy ray curable resin composition and, if necessary, a solvent is prepared, and then, this coating liquid is applied to a substrate by a known method, and the obtained coating film is cured to form a hard coat layer made of a cured product of the active energy ray curable resin composition. In addition, if necessary, a drying treatment may be performed before curing the coating film.
[0036] Examples of solvents used in preparing the coating liquid include aromatic hydrocarbon solvents such as benzene and toluene; ester solvents such as ethyl acetate and butyl acetate; ketone solvents such as acetone, methyl ethyl ketone and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as n-pentane, n-hexane and n-heptane; and alicyclic hydrocarbon solvents such as cyclopentane and cyclohexane. These solvents can be used alone or in combination of two or more.
[0037] Examples of the coating method include bar coating, spin coating, dipping, roll coating, gravure coating, knife coating, air knife coating, roll knife coating, die coating, screen printing, spray coating, and gravure offset.
[0038] When drying the coating film, a conventionally known drying method such as hot air drying, heated roll drying, infrared irradiation, etc. can be used as the drying method. The drying temperature is usually in the range of 60 to 130° C. The drying time is usually from several seconds to several tens of minutes.
[0039] The coating film can be cured by irradiating the coating film with active energy rays. Examples of the active energy ray include ultraviolet rays, electron beams, α rays, β rays, γ rays, etc. Among these, the active energy ray is preferably an electron beam or ultraviolet rays, more preferably ultraviolet rays, since it can be generated using a relatively simple device. When ultraviolet rays are used as the active energy rays, the ultraviolet light source may be an ultra-high pressure mercury lamp, a high pressure mercury lamp, a low pressure mercury lamp, a carbon arc, a black light lamp, a metal halide lamp, or the like. There is no particular limitation on the amount of ultraviolet light, but it is usually 100 mJ / cm. 2 ~1,000mJ / cm 2 The irradiation time is usually from a few seconds to a few hours, and the irradiation temperature is usually from room temperature to 100°C.
[0040] The thickness of the hard coat layer is usually 20 μm or less, preferably 0.5 to 20 μm, and more preferably 1.0 to 10 μm.
[0041] The antistatic layer is not particularly limited, but is preferably made of a composition for forming an antistatic layer containing a metal alkoxide and / or a condensation polymer of a partial hydrolyzate of a metal alkoxide. By providing this antistatic layer, antistatic properties are imparted to the gas barrier laminate. Metal alkoxides are generally represented by M(OR)n, and the metal M is not particularly limited and may be an alkali metal such as lithium, sodium, or potassium; magnesium; alkaline earth metals such as calcium, strontium, or barium; elements of Group 3 of the periodic table such as scandium or yttrium; elements of Group 4 of the periodic table such as titanium, zirconium, or hafnium; elements of Group 5 of the periodic table such as vanadium, niobium, or tantalum; elements of Group 6 of the periodic table such as molybdenum or tungsten; iron, etc. Examples of the metal alkoxide include Group 8 elements of the periodic table, such as zinc; Group 12 elements of the periodic table, such as boron, aluminum, gallium, indium; Group 14 elements of the periodic table, such as silicon, germanium, tin, lead; Group 15 elements of the periodic table, such as phosphorus, antimony, bismuth; and lanthanoids, such as lanthanum. Among these, silicon is most preferred from the viewpoint of high antistatic properties and high adhesion to the smoothing layer. That is, tetraalkoxysilane is most preferred. The above metal alkoxides may be used alone or in combination of multiple types of metal alkoxides. R represents an alkyl group, and in the present invention, an alkyl group having 1 to 10 carbon atoms is preferable, and an alkyl group having 1 to 5 carbon atoms is more preferable. When a metal alkoxide has a plurality of alkyl groups, they may be the same or different. n is an integer determined by the valence of the metal M, and is usually in the range of 1 to 5. These metal alkoxides may be partially hydrolyzed in advance. Even if the metal alkoxide is mixed with a partially hydrolyzed metal alkoxide, good.
[0042] The composition for forming the antistatic layer preferably contains fine particles such as organic fine particles and inorganic fine particles. By using the composition for forming the antistatic layer containing fine particles, the surface roughness of the antistatic layer can be efficiently controlled. As such fine particles, the same ones as those described in the description of the hard coat layer can be used.
[0043] The method for forming the antistatic layer is not particularly limited, and various methods can be used, but it is preferable to form the layer by applying a coating liquid containing a metal alkoxide and / or a partial hydrolysate of a metal alkoxide. The coating method of the coating liquid can be a commonly used method. For example, gravure coating, bar coating, spray coating, spin coating, etc. can be mentioned. When coating, the metal alkoxide and / or the partial hydrolyzate of the metal alkoxide can be dissolved in a solvent and applied, and an organic solvent can be preferably used. The organic solvent that can be used is not particularly limited, and for example, an alcohol solvent such as ethanol or isopropanol, or a ketone solvent such as methyl ethyl ketone can be used. The above metal alkoxide and / or partial hydrolysate of a metal alkoxide undergoes a hydrolysis reaction and a polycondensation reaction to form a condensation polymer, thereby forming an antistatic layer. An acid catalyst such as hydrochloric acid or nitric acid may be added to promote the hydrolysis reaction. In addition, after the metal alkoxide and / or the partial hydrolysate of the metal alkoxide is applied by the above method, it is preferable to perform a heat treatment for the purpose of drying and promoting the polycondensation reaction of the metal alkoxide and / or the partial hydrolysate of the metal alkoxide. The heating conditions are not particularly limited as long as the above purpose can be achieved, but it is usually preferable to perform the heating at a temperature in the range of 40 to 120°C for a heating time of about 20 seconds to 5 minutes. From the viewpoints of productivity and preventing the occurrence of wrinkles due to heat shrinkage, it is more preferable to perform the heating at a temperature in the range of 60 to 110°C for a heating time of about 30 seconds to 2 minutes.
[0044] The thickness of the antistatic layer is usually 20 μm or less, preferably 0.05 to 10 μm, and more preferably 0.08 to 3 μm.
[0045] The arithmetic mean roughness (Ra) of the functional layer surface (the surface of the functional layer opposite to the substrate side) is preferably 5 nm or more, more preferably 5 to 20 nm, and even more preferably 5 to 10 nm. The maximum profile height (Rt) of the roughness curve of the functional layer surface is preferably 100 nm or more, more preferably 100 to 1000 nm, and even more preferably 100 to 800 nm. When the functional layer surface has such roughness, a gas barrier laminate having the friction characteristics described below can be efficiently obtained. The arithmetic mean roughness (Ra) and the maximum cross-sectional height (Rt) of the roughness curve of the surface of the functional layer or the surface of other layers can be determined by observing an area of 500 μm × 500 μm using an optical interference microscope.
[0046] (3) Smoothing layer The smoothing layer constituting the gas barrier laminate of the present invention serves to reduce the unevenness of the substrate surface and to improve the interlayer adhesion of the gas barrier laminate.
[0047] The smoothing layer may be, for example, a layer made of a cured product of an active energy ray-curable resin composition. Examples of the active energy ray-curable resin composition include the same active energy ray-curable resin composition for forming the hard coat layer. However, since the smoothing layer is preferably superior in smoothness to the functional layer, it is preferable that the smoothing layer does not contain components that roughen the surface of the smoothing layer, such as the fine particles. The smoothing layer can be formed by the same method as that for forming the hard coat layer.
[0048] The thickness of the smoothing layer is usually 20 μm or less, preferably 0.1 to 20 μm, and more preferably 0.5 to 10 μm.
[0049] The arithmetic mean roughness (Ra) of the smoothing layer surface (the surface of the smoothing layer opposite to the substrate side) is preferably 5 nm or less, more preferably 0.1 to 5 nm, even more preferably 0.1 to 4 nm, and particularly preferably 1 to 4 nm. The maximum profile height (Rt) of the roughness curve of the smoothing layer surface is preferably 100 nm or less, more preferably 1 to 100 nm, further preferably 20 to 80 nm, and particularly preferably 30 to 65 nm. When the smoothing layer surface has such roughness, the interlayer adhesion of the gas barrier laminate is improved, and a gas barrier laminate having the friction characteristics described below can be efficiently obtained.
[0050] (4) Gas barrier layer The gas barrier layer constituting the gas barrier laminate of the present invention is a layer having the property of suppressing the permeation of gases such as oxygen and water vapor (gas barrier property).
[0051] Examples of the gas barrier layer include those obtained by subjecting an inorganic vapor deposition film or a layer containing a polymer (hereinafter, sometimes referred to as a "polymer layer") to a modification treatment (in this case, the gas barrier layer does not mean only the region modified by ion implantation treatment or the like, but means "a polymer layer including a modified region").
[0052] Examples of the inorganic vapor deposition film include vapor deposition films of inorganic compounds and metals. Raw materials for the vapor deposition film of an inorganic compound include inorganic oxides such as silicon oxide, aluminum oxide, magnesium oxide, zinc oxide, indium oxide, and tin oxide; inorganic nitrides such as silicon nitride, aluminum nitride, and titanium nitride; inorganic carbides; inorganic sulfides; inorganic oxynitrides such as silicon oxynitride; inorganic oxycarbides; inorganic carbide nitrides; and inorganic oxynitride carbides. Examples of materials for the metal vapor deposition film include aluminum, magnesium, zinc, and tin. These may be used alone or in combination of two or more. Among these, from the viewpoint of gas barrier properties, inorganic vapor deposition films made from inorganic oxides, inorganic nitrides, or metals are preferred, and from the viewpoint of transparency, inorganic vapor deposition films made from inorganic oxides or inorganic nitrides are more preferred.
[0053] Methods for forming inorganic vapor deposition films include PVD (physical vapor deposition) methods such as vacuum deposition, sputtering, and ion plating, and CVD methods such as thermal CVD (chemical vapor deposition), plasma CVD, and photo CVD.
[0054] The thickness of the inorganic vapor deposition film varies depending on the inorganic compound used, but from the viewpoints of gas barrier properties and ease of handling, it is preferably in the range of 50 to 300 nm, more preferably 50 to 200 nm.
[0055]
[0043] Examples of the polymer used in the gas barrier layer obtained by subjecting a polymer layer to a modification treatment include silicon-containing polymers, polyimides, polyamides, polyamideimides, polyphenylene ethers, polyether ketones, polyether ether ketones, polyolefins, polyesters, polycarbonates, polysulfones, polyether sulfones, polyphenylene sulfide, polyarylates, acrylic resins, cycloolefin polymers, and aromatic polymers. These polymers can be used alone or in combination of two or more.
[0056] Among these, the polymer is preferably a silicon-containing polymer, since it can form a gas barrier layer with better gas barrier properties. Examples of the silicon-containing polymer include polysilazane-based compounds, polycarbosilane-based compounds, polysilane-based compounds, and polyorganosiloxane-based compounds. Among these, polysilazane-based compounds are preferred, since it can form a gas barrier layer with excellent gas barrier properties even if it is thin. By subjecting a layer containing a polysilazane-based compound to a modification treatment, it is possible to form a layer (silicon oxynitride layer) having oxygen, nitrogen, and silicon as main constituent atoms.
[0057] A polysilazane compound is a polymer having a repeating unit containing a -Si-N- bond (silazane bond) in the molecule. Specifically, the polysilazane compound is represented by the formula (1):
[0058] [ka]
[0059] It is preferable to use a compound having a repeating unit represented by the following formula: Furthermore, the number average molecular weight of the polysilazane compound used is not particularly limited, but is preferably 100 to 50,000.
[0060] In the formula (1), n represents an arbitrary natural number. Rx, Ry, and Rz each independently represent a non-hydrolyzable group such as a hydrogen atom, an unsubstituted or substituted alkyl group, an unsubstituted or substituted cycloalkyl group, an unsubstituted or substituted alkenyl group, an unsubstituted or substituted aryl group, or an alkylsilyl group.
[0061] Examples of the alkyl group of the unsubstituted or substituted alkyl group include alkyl groups having 1 to 10 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a t-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, an n-hexyl group, an n-heptyl group, and an n-octyl group.
[0062] Examples of the cycloalkyl group of the unsubstituted or substituted cycloalkyl group include cycloalkyl groups having 3 to 10 carbon atoms, such as a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, and a cycloheptyl group.
[0063] Examples of the alkenyl group of the unsubstituted or substituted alkenyl group include alkenyl groups having 2 to 10 carbon atoms, such as a vinyl group, a 1-propenyl group, a 2-propenyl group, a 1-butenyl group, a 2-butenyl group, and a 3-butenyl group.
[0064] Examples of the substituent on the alkyl group, cycloalkyl group, and alkenyl group include halogen atoms such as a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom; a hydroxyl group; a thiol group; an epoxy group; a glycidoxy group; a (meth)acryloyloxy group; and unsubstituted or substituted aryl groups such as a phenyl group, a 4-methylphenyl group, and a 4-chlorophenyl group.
[0065] Examples of the aryl group of the unsubstituted or substituted aryl group include aryl groups having 6 to 10 carbon atoms, such as a phenyl group, a 1-naphthyl group, and a 2-naphthyl group.
[0066] Examples of the substituent on the aryl group include halogen atoms such as a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom; alkyl groups having 1 to 6 carbon atoms such as a methyl group and an ethyl group; alkoxy groups having 1 to 6 carbon atoms such as a methoxy group and an ethoxy group; a nitro group; a cyano group; a hydroxyl group; a thiol group; an epoxy group; a glycidoxy group; a (meth)acryloyloxy group; and unsubstituted or substituted aryl groups such as a phenyl group, a 4-methylphenyl group, and a 4-chlorophenyl group.
[0067] Examples of the alkylsilyl group include a trimethylsilyl group, a triethylsilyl group, a triisopropylsilyl group, a tri-t-butylsilyl group, a methyldiethylsilyl group, a dimethylsilyl group, a diethylsilyl group, a methylsilyl group, and an ethylsilyl group.
[0068] Among these, Rx, Ry and Rz are preferably a hydrogen atom, an alkyl group having 1 to 6 carbon atoms or a phenyl group, and more preferably a hydrogen atom.
[0069] The polysilazane compound having a repeating unit represented by the formula (1) may be either an inorganic polysilazane in which Rx, Ry, and Rz are all hydrogen atoms, or an organic polysilazane in which at least one of Rx, Ry, and Rz is not a hydrogen atom. In addition, in the present invention, modified polysilazane can also be used as the polysilazane-based compound.As modified polysilazane, for example, those described in JP-A-62-195024, JP-A-2-84437, JP-A-63-81122, JP-A-1-138108, JP-A-2-175726, JP-A-5-238827, JP-A-5-238827, JP-A-6-122852, JP-A-6-306329, JP-A-6-299118, JP-A-9-31333, JP-A-5-345826, JP-A-4-63833, etc. can be mentioned. Among these, the polysilazane compound is preferably perhydropolysilazane, in which Rx, Ry, and Rz are all hydrogen atoms, from the viewpoints of availability and ability to form an ion-implanted layer having excellent gas barrier properties. As the polysilazane compound, commercially available products available as glass coating materials and the like can be used as they are. The polysilazane compounds can be used alone or in combination of two or more.
[0070] In addition to the above-mentioned polymer, the polymer layer may contain other components within the scope of not impairing the object of the present invention. Examples of other components include a curing agent, an antiaging agent, a light stabilizer, and a flame retardant. The content of the polymer in the polymer layer is preferably 50% by mass or more, and more preferably 70% by mass or more, since a gas barrier layer having better gas barrier properties can be obtained.
[0071] The thickness of the polymer layer is not particularly limited, but is preferably in the range of 50 to 300 nm, more preferably 50 to 200 nm. In the present invention, even if the thickness of the polymer layer is on the nano-order, a gas barrier laminate having sufficient gas barrier properties can be obtained.
[0072] The method for forming the polymer layer is not particularly limited. For example, a polymer layer forming solution containing at least one polymer, optionally other components, a solvent, etc. is prepared, and then the polymer layer forming solution is applied by a known method, and the resulting coating film is dried, thereby forming the polymer layer.
[0073] Examples of solvents used in the polymer layer forming solution include aromatic hydrocarbon solvents such as benzene and toluene; ester solvents such as ethyl acetate and butyl acetate; ketone solvents such as acetone, methyl ethyl ketone and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as n-pentane, n-hexane and n-heptane; and alicyclic hydrocarbon solvents such as cyclopentane and cyclohexane. These solvents can be used alone or in combination of two or more.
[0074] Examples of the method for applying the polymer layer-forming solution include bar coating, spin coating, dipping, roll coating, gravure coating, knife coating, air knife coating, roll knife coating, die coating, screen printing, spray coating, and gravure offset.
[0075] The method for drying the formed coating film can be a conventionally known drying method such as hot air drying, heated roll drying, infrared irradiation, etc. The heating temperature is usually in the range of 60 to 130° C. The heating time is usually from several seconds to several tens of minutes.
[0076] Examples of the modification treatment of the polymer layer include ion implantation treatment, plasma treatment, ultraviolet irradiation treatment, and heat treatment. As described below, the ion implantation process is a method of modifying a polymer layer by implanting ions into the polymer layer. The plasma treatment is a method of modifying a polymer layer by exposing the polymer layer to plasma. For example, the plasma treatment can be performed according to the method described in JP 2012-106421 A. The ultraviolet irradiation treatment is a method of modifying a polymer layer by irradiating the polymer layer with ultraviolet rays. For example, the ultraviolet modification treatment can be performed according to the method described in JP 2013-226757 A. Among these, ion implantation is preferred because it efficiently modifies the inside of the polymer layer without roughening the surface thereof, and can form a gas barrier layer with better gas barrier properties.
[0077] Examples of ions to be injected into the polymer layer include ions of rare gases such as argon, helium, neon, krypton, xenon, etc.; ions of fluorocarbons, hydrogen, nitrogen, oxygen, carbon dioxide, chlorine, fluorine, sulfur, etc.; ions of alkane gases such as methane and ethane; ions of alkene gases such as ethylene and propylene; ions of alkadiene gases such as pentadiene and butadiene; ions of alkyne gases such as acetylene; ions of aromatic hydrocarbon gases such as benzene and toluene; ions of cycloalkane gases such as cyclopropane; ions of cycloalkene gases such as cyclopentene; ions of metals; and ions of organosilicon compounds. These ions can be used alone or in combination of two or more. Among these, ions of rare gases such as argon, helium, neon, krypton, and xenon are preferred because they can be implanted more easily and provide a gas barrier layer with better gas barrier properties.
[0078] The amount of ions to be implanted can be appropriately determined depending on the intended use of the gas barrier laminate (required gas barrier properties, transparency, etc.), etc.
[0079] Methods for injecting ions include a method of irradiating ions (ion beam) accelerated by an electric field, a method of injecting ions in plasma, etc. Among these, in the present invention, the latter method of injecting plasma ions is preferred because the desired barrier layer can be easily obtained.
[0080] Plasma ion implantation can be performed, for example, by generating plasma in an atmosphere containing a plasma generating gas such as a rare gas, and applying a negative high voltage pulse to the polymer layer, thereby injecting ions (cations) in the plasma into the surface portion of the polymer layer.
[0081] The thickness of the region into which ions are implanted by ion implantation can be controlled by the implantation conditions such as the type of ion, applied voltage, and treatment time, and may be determined depending on the thickness of the polymer layer, the intended use of the laminate, etc., but is usually 10 to 300 nm.
[0082] (4) Long gas barrier laminate The long gas barrier laminate of the present invention is characterized in that the functional layer is laminated on one side of the substrate, and the smoothing layer and the gas barrier layer are laminated in this order on the other side of the substrate, and the static friction coefficient between the side of the functional layer opposite the substrate and the side of the gas barrier layer opposite the substrate is 0.35 to 0.80.
[0083] The static friction coefficient between the surface of the functional layer opposite the substrate side and the surface of the gas barrier layer opposite the substrate side is 0.35 to 0.80, and preferably 0.40 to 0.75. When the static friction coefficient between the functional layer and the gas barrier layer is within the above range, problems such as blocking and air entrapment are less likely to occur when the long gas barrier laminate of the present invention is wound into a roll or unwound from the roll.
[0084] In the long gas barrier laminate of the present invention, the static friction coefficient between the surface of the functional layer opposite the substrate side and the surface of the smoothing layer opposite the substrate side is preferably 0.35 to 0.80, and more preferably 0.40 to 0.75. When the static friction coefficient between the functional layer and the smoothing layer is within the above range, problems such as blocking and air entrapment are less likely to occur when the resin film with the functional layer and smoothing layer, which is a manufacturing intermediate for the long gas barrier laminate of the present invention, is wound into a roll or unwound from the roll. The static friction coefficients of the functional layer, smoothing layer, and gas barrier layer can be measured in accordance with JIS K7125.
[0085] The long gas barrier laminate of the present invention may have a layer structure of functional layer / substrate / smoothing layer / gas barrier layer. The long gas barrier laminate of the present invention may have layers other than the functional layer, the substrate, the smoothing layer and the gas barrier layer. Examples of layers other than the substrate, the smoothing layer, and the gas barrier layer include a conductive layer, an impact absorbing layer, an adhesive layer, a process sheet, etc. The process sheet has a role of protecting the laminate when the laminate is stored, transported, etc., and is peeled off when the laminate is used. The gas barrier laminate of the present invention can be produced by the method described below.
[0086] The thickness of the gas barrier laminate of the present invention is not particularly limited, but is preferably 5 to 100 μm, more preferably 10 to 50 μm, and further preferably 20 to 40 μm.
[0087] The water vapor transmission rate of the gas barrier laminate of the present invention at a temperature of 40° C. and a relative humidity of 90% is preferably 0.1 g / (m 2 ·day) or less, more preferably 0.05g / (m 2 ·day) or less, more preferably 0.03 g / (m 2 ·day) or less. There is no particular lower limit, and the smaller the better, but it is usually 0.001g / (m 2 ·day) or more. The water vapor transmission rate can be measured by the method described in the examples.
[0088] Since the gas barrier laminate of the present invention has excellent gas barrier properties, it is suitably used as a member for electronic devices. Examples of electronic devices include liquid crystal displays, organic EL displays, inorganic EL displays, electronic paper, and solar cells.
[0089] 2) Method for producing a long gas barrier laminate The production method of the present invention is a method for producing a long gas barrier laminate of the present invention, and is a production method (a) having the following steps (aI) to (a-III) or a production method (b) having the following steps (bI) to (b-III).
[0090] [Manufacturing method (a)] A step (aI) of forming a smoothing layer on the resin film while transporting the resin film from a roll of the substrate resin film in a certain direction, and then winding up the obtained resin film with the smoothing layer into a roll. A step (a-II) of continuously unwinding the resin film from the roll of the resin film with the smoothing layer obtained in step (aI) and transporting the resin film in a constant direction while forming a functional layer on the resin film surface of the resin film with the smoothing layer, and then winding up the resulting functional layer and resin film with the smoothing layer into a roll. a step (a-III) of continuously unwinding the resin film from the roll of the resin film with the functional layer and the smoothing layer obtained in step (a-II) and transporting the resin film in a constant direction while forming a gas barrier layer having a static friction coefficient with the functional layer of 0.35 to 0.80 on the surface of the smoothing layer of the resin film with the functional layer and the smoothing layer, and then winding up the resulting gas barrier laminate into a roll;
[0091] Step (aI) is a step of forming a smoothing layer on a substrate resin film while transporting the resin film in a certain direction, and then winding up the obtained resin film with a smoothing layer into a roll.
[0092] The resin film for substrate to be used and the method for forming the smoothing layer may be the same as those described above. As a method for transporting the resin film and a method for winding up the resin film with the smoothing layer after the formation of the smoothing layer, a conventional laminated film manufacturing method using a roll-to-roll system can be used.
[0093] Step (a-II) is a step in which the resin film is continuously unwound from the roll of resin film with smoothing layer obtained in step (aI) and transported in a constant direction while forming a functional layer on the resin film surface of the resin film with smoothing layer, and then the resulting functional layer and resin film with smoothing layer are wound into a roll. In step (a-II), the static friction coefficient between the surface of the smoothing layer opposite the substrate side and the surface of the functional layer opposite the substrate side is preferably 0.35 to 0.80, more preferably 0.40 to 0.75. When the static friction coefficient between the functional layer and the smoothing layer is within the above range, problems such as blocking and air entrapment are less likely to occur when the resin film with the functional layer and smoothing layer, which is a production intermediate of a long gas barrier laminate, is wound into a roll or unwound from the roll.
[0094] The method for forming the functional layer may be the same as that described above. The method of unwinding and transporting the resin film with smoothing layer from the roll, and the method of winding up the functional layer and the resin film with smoothing layer after the functional layer is formed can utilize conventional laminated film manufacturing methods using the roll-to-roll method.
[0095] Step (a-III) is a step in which the resin film is continuously unwound from the roll of resin film with functional layer and smoothing layer obtained in step (a-II) and transported in a constant direction while forming a gas barrier layer having a static friction coefficient with the functional layer of 0.35 to 0.80 on the surface of the smoothing layer of the resin film with functional layer and smoothing layer, and then the resulting gas barrier laminate is wound into a roll.
[0096] The gas barrier layer provided on the smoothing layer usually has excellent smoothness, and therefore a gas barrier laminate having such a gas barrier layer is also prone to problems such as blocking and air entrapment when it is wound into a roll or unwound from the roll. In the present invention, these problems can be solved by controlling the coefficient of friction between the functional layer and the gas barrier layer.
[0097] The gas barrier layer can be formed by the same method as described above. The method for unwinding and transporting the resin film with the functional layer and smoothing layer from the roll, and the method for winding up the gas barrier laminate after the gas barrier layer is formed, can utilize conventional laminate film manufacturing methods using a roll-to-roll system.
[0098] [Manufacturing method (b)] A step (bI) of forming a functional layer on a substrate resin film while transporting the substrate resin film in a certain direction, and then winding up the resulting functional layer-coated resin film into a roll. A step (b-II) of continuously unwinding the resin film from the roll of the functional layer-attached resin film obtained in step (bI) and transporting the resin film in a constant direction while forming a smoothing layer on the resin film surface of the functional layer-attached resin film, and then winding up the resulting functional layer and smoothing layer-attached resin film into a roll. a step (b-III) of continuously unwinding the resin film from the roll of the functional layer and smoothing layer-attached resin film obtained in step (b-II) and transporting the resin film in a constant direction while forming a gas barrier layer having a static friction coefficient with the functional layer of 0.35 to 0.80 on the surface of the smoothing layer of the functional layer and smoothing layer-attached resin film, and then winding up the resulting gas barrier laminate into a roll;
[0099] Step (bI) is a step of forming a functional layer on a substrate resin film while transporting the resin film in a certain direction, and then winding up the resulting resin film with a functional layer into a roll. Step (b-1) is the same as step (a-1), except that a functional layer is formed instead of a smoothing layer.
[0100] Step (b-II) is a step in which the resin film is continuously unwound from the roll of resin film with functional layer obtained in step (bI) and transported in a constant direction while forming a smoothing layer on the resin film surface of the resin film with functional layer, and then the resulting resin film with functional layer and smoothing layer is wound into a roll. Step (b-II) is the same as step (a-II) except that a smoothing layer is formed instead of a functional layer. In step (b-II), the static friction coefficient between the surface of the functional layer opposite the substrate side and the surface of the smoothing layer opposite the substrate side is preferably 0.35 to 0.80, more preferably 0.40 to 0.75. When the static friction coefficient between the functional layer and the smoothing layer is within the above range, problems such as blocking and air entrapment are less likely to occur when the resin film with the functional layer and smoothing layer, which is a production intermediate of a long gas barrier laminate, is wound into a roll or unwound from the roll.
[0101] Step (b-III) is a step in which the resin film is continuously unwound from the roll-shaped resin film with functional layer and smoothing layer obtained in step (b-II) and transported in a constant direction while forming a gas barrier layer having a static friction coefficient with the functional layer of 0.35 to 0.80 on the surface of the smoothing layer of the resin film with functional layer and smoothing layer, and then the resulting gas barrier laminate is wound into a roll. Step (b-III) is the same as step (a-III).
[0102] According to the method of the present invention [production method (a) or (b)], a long gas barrier laminate of the present invention can be efficiently produced. EXAMPLES
[0103] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples in any way. In each example, parts and percentages are by weight unless otherwise specified.
[0104] (Measurement of thickness of each layer of gas barrier laminate) The thickness of each layer of the gas barrier laminate obtained in the examples and comparative examples was measured using a stylus type step gauge (XP-1, manufactured by AMBIOS TECHNOLOGY).
[0105] (Smoothness of each layer) The smoothness of each layer in the gas barrier laminates or intermediate products thereof obtained in the Examples and Comparative Examples was measured using an optical interference microscope (Veeco Corporation, "NT1100") at 250,000 μm. 2 Each layer was observed over an area of (500 μm × 500 μm), and the arithmetic mean roughness (Ra) and the maximum cross-sectional height of the roughness curve (Rt) were determined.
[0106] (Static friction coefficient) In the gas barrier laminates obtained in the examples and comparative examples, a surface of the functional layer opposite to the substrate side; Gas Barrier The static friction coefficient between the layer and the surface opposite to the substrate (in Table 1, the static friction coefficient 2 ) and the static friction coefficient between the surface of the functional layer opposite the substrate side and the surface of the smoothing layer opposite the substrate side in the resin film with the functional layer and smoothing layer, which is an intermediate product for the production of the gas barrier laminate (indicated as "static friction coefficient" in Table 1). 1 and (denoted as "1" and "2") were measured in accordance with JIS K7125 by preparing two gas barrier laminates or intermediate products thereof, stacking them so that the specified layers faced each other, and measuring the gas barrier properties in accordance with JIS K7125.
[0107] (Winding property evaluation) The long gas barrier laminates 1 to 5 obtained in Examples 1 to 3 and Comparative Example 1 were wound into a roll, and the winding properties were evaluated according to the following criteria. The evaluation results are shown in Table 1. ◯: Neither blocking nor air entrapment occurs. ×: At least either blocking or air entrapment occurred.
[0108] (Pencil hardness) The surfaces of the functional layers of the gas barrier laminates obtained in the Examples and Comparative Examples were measured for hardness by the pencil method using a pencil scratch coating hardness tester (manufactured by Toyo Seiki Seisakusho, model "NP") in accordance with JIS K 5600-5-4.
[0109] (Surface resistivity) The surface resistivity of the functional layer side of the gas barrier laminates obtained in the Examples and Comparative Examples was measured using parallel electrodes connected to a digital electrometer (manufactured by Advantest Corporation).
[0110] (Anti-glare) The gas barrier laminates obtained in the Examples and Comparative Examples were placed on a black plate with the functional layer facing up. Next, a three-wavelength fluorescent lamp was turned on above the functional layer, and the light was reflected by the functional layer and evaluated according to the following criteria. The results are shown in Table 2. ○: The outline of the fluorescent light is blurred due to reflection from the functional layer. ×: The outline of the fluorescent light is not blurred due to reflection from the functional layer.
[0111] [Production Example 1] 20 parts of dipentaerythritol hexaacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., product name: A-DPH) was dissolved in 100 parts of methyl isobutyl ketone, and then 3 parts of a photopolymerization initiator (manufactured by BASF, product name: Irgacure 127) was added to prepare a solution for forming a smoothing layer.
[0112] [Production Example 2] A resin film (1) was unwound from a roll of polyethylene terephthalate film (manufactured by Teijin DuPont, product name: PET25 Tetoron HPE, thickness: 25 μm, referred to as "resin film (1)"; the same applies below). While the resin film (1) was being transported, the smoothing layer-forming solution obtained in Production Example 1 was applied onto the resin film (1) by a bar coating method. The resulting coating film was dried by heating at 70° C. for 1 minute, and then irradiated with UV light using a UV light irradiation line (high pressure mercury lamp, line speed: 20 m / min, accumulated light amount: 100 mJ / cm ). 2The smoothing layer was formed at a thickness of 1 μm under the conditions of 100 nm (peak intensity: 1.466 W, number of passes: 2), and the obtained resin film with the smoothing layer was wound up in a roll.
[0113] (Production Example 3) 100 parts of a urethane-based hard coating agent containing a photopolymerization initiator (manufactured by Arakawa Chemical Industries, Ltd., product name: Beamset 575CB, solid content 100%) was uniformly mixed with 5 parts of spherical silicone bead particles (manufactured by Momentive Performance Materials Japan, Inc., product name: Tospearl 130, average particle size 3.0 μm, solid content 100%), 61.6 parts of ethyl cellosolve, and 61.6 parts of isobutanol to prepare a hard coating layer forming solution (1) with a solid content of 46%. Next, the resin film with the smoothing layer obtained in Production Example 2 was unwound from the roll, and while the resin film was being transported, the hard coat layer forming solution (1) was applied to the surface of the resin film by a bar coating method. The resulting coating film was dried by heating at 70° C. for 1 minute, and then irradiated with UV light using a UV light irradiation line (high pressure mercury lamp, line speed: 20 m / min, accumulated light amount: 100 mJ / cm 2 ). 2 The resulting resin film (1) with hard coat layer A and smoothing layer having a layer structure of hard coat layer A / resin film / smoothing layer was wound into a roll.
[0114] (Production Example 4) 100 parts of a silicate coating liquid (manufactured by Colcoat Co., Ltd., product name: Colcoat N103-X, solid content 2%), which is a hydrolysis and dehydration condensation compound of tetraethoxylan, was uniformly mixed with 0.1 parts of spherical silicone bead particles (manufactured by Momentive Performance Materials Japan, Inc., product name: Tospearl 130, average particle size 3.0 μm, solid content 100%) to prepare an antistatic layer forming solution (2) with a solid content of 2%. Next, the resin film with the smoothing layer obtained in Manufacturing Example 2 was unwound from the roll, and while the resin film was being transported, the antistatic layer forming solution (2) was applied to the resin film surface by a bar coating method. The resulting coating was heated and dried at 70°C for 1 minute to form an antistatic layer A with a thickness of 100 nm. The resulting antistatic layer A and resin film with the smoothing layer (2) having a layer structure of antistatic layer A / resin film / smoothing layer was wound into a roll.
[0115] (Production Example 5) 100 parts of dipentaerythritol hexaacrylate (NK Ester A-DPH, manufactured by Shin-Nakamura Chemical Co., Ltd.) as a polyfunctional (meth)acrylate, 3 parts of 1-hydroxycyclohexyl phenyl ketone (Irgacure 184, manufactured by BASF) as a photopolymerization initiator, 5 parts of silicone resin microparticles (Tospearl 120, manufactured by Momentive Corporation, volume average particle size: 2 μm), and 18 parts of silica nanoparticles (MIBK-ST, manufactured by Nissan Chemical Industries, Ltd., average particle size: 10 nm) were mixed and then diluted with propylene glycol monomethyl ether to obtain an antiglare hard coat layer forming solution (3) with a solids concentration of 30%. Next, the resin film with the smoothing layer obtained in Production Example 2 was unwound from the roll, and while the resin film was being transported, the antiglare hard coat layer forming solution (3) was applied to the resin film surface by a bar coating method. The resulting coating film was dried by heating at 70°C for 1 minute, and then irradiated with UV light using a UV light irradiation line (high pressure mercury lamp, line speed: 20 m / min, accumulated light amount: 100 mJ / cm2). 2 The antiglare hard coat layer A having a thickness of 2 μm was formed under the conditions of 1.05 mm thickness, 1.0 ...
[0116] (Production Example 6) In Production Example 3, except that the smoothing layer forming solution was used as the hard coat layer forming solution instead of the hard coat layer forming solution (1), a hard coat layer B and a resin film with a smoothing layer (4) having a layer structure of hard coat layer B / resin film / smoothing layer was wound into a roll.
[0117] (Production Example 7) In Production Example 4, an antistatic layer B was prepared in the same manner as in Example 2, except that no spherical silicone bead microparticles were added, and the antistatic layer B and the resin film with smoothing layer (5) having a layer structure of antistatic layer B / resin film / smoothing layer were wound into a roll.
[0118] Example 1 The resin film (1) with hard coat layer A and smoothing layer obtained in Production Example 3 was unwound from the roll, and while the resin film (1) was being conveyed, perhydropolysilazane (manufactured by AZ Electronic Materials, product name: AZNL110A-20) was applied to the smoothing layer surface by a bar coating method, and the resulting coating was heated at 120°C for 2 minutes to form a perhydropolysilazane layer with a thickness of 150 nm. Thereafter, as a modification treatment, argon (Ar) was plasma ion-injected into the surface of the perhydropolysilazane layer using a plasma ion injection device to form a gas barrier layer, and a long gas barrier laminate 1 having a layer structure of hard coat layer A / substrate (resin film) / smoothing layer / gas barrier layer was obtained. The surface roughness, static friction coefficient, winding property, pencil hardness, surface resistivity and antiglare property of each layer of the long gas barrier laminate 1 are shown in Table 1.
[0119] The plasma ion implantation apparatus and plasma ion implantation conditions used for forming the gas barrier layer are as follows. (Plasma ion implantation equipment) RF power supply: Model number "RF" 56000, manufactured by JEOL Ltd. High voltage pulse power supply: "PV-3-HSHV-0835", manufactured by Kurita Manufacturing Co., Ltd. (Plasma ion implantation conditions) Plasma generating gas: Ar Gas flow rate: 100sccm ·Duty ratio: 0.5% Repetition rate: 1000Hz Applied voltage: -10kV ·RF power supply: Frequency 13.56MHz, applied power 1000W Chamber pressure: 0.2Pa Pulse width: 5μsec Processing time (ion implantation time): 5 minutes Conveying speed: 0.2m / min
[0120] Example 2 A long gas barrier laminate 2 was obtained in the same manner as in Example 1, except that in Example 1, the antistatic layer A and the resin film with smoothing layer (2) obtained in Production Example 4 were used instead of the hard coat layer A and the resin film with smoothing layer (1). Table 1 shows the surface roughness and static friction coefficient of each layer of the long gas barrier laminate 2.
[0121] Example 3 A long gas barrier laminate 3 was obtained in the same manner as in Example 1, except that in Example 1, the hard coat layer A and the resin film with smoothing layer (1) were replaced with the antiglare layer and the resin film with smoothing layer (3) obtained in Production Example 5. Table 1 shows the surface roughness and static friction coefficient of each layer of the long gas barrier laminate 3.
[0122] Comparative Example 1 A long gas barrier laminate 4 was obtained in the same manner as in Example 1, except that in Example 1, the hard coat layer A and the resin film with smoothing layer (1) were replaced with the hard coat layer B and the resin film with smoothing layer (4) obtained in Production Example 6. Table 1 shows the surface roughness and static friction coefficient of each layer of the long gas barrier laminate 4.
[0123] Comparative Example 2 A long gas barrier laminate 5 was obtained in the same manner as in Example 1, except that in Example 1, the hard coat layer A and the resin film with smoothing layer (1) were replaced with the antistatic layer B and the resin film with smoothing layer (5) obtained in Production Example 7. Table 1 shows the surface roughness and static friction coefficient of each layer of the long gas barrier laminate 5.
[0124] [Table 1]
[0125] From Table 1, we can see the following: The gas barrier laminates of Examples 1 to 3 were excellent in winding property since no blocking or air entrapment occurred when the laminates were wound up. On the other hand, the gas barrier laminates of Comparative Examples 1 and 2 were inferior in winding property because blocking and air entrapment occurred during winding.
Claims
1. A long gas barrier laminate comprising a functional layer laminated on one surface side of a substrate, and a smoothing layer and a gas barrier layer laminated in this order on the other surface side of the substrate, the functional layer is formed from an active energy ray-curable resin composition containing fine particles, The surface of the functional layer opposite to the substrate has an arithmetic average roughness (Ra) of 5 to 14.7 nm and a maximum profile height (Rt) of the roughness curve of 100 to 1000 nm; A long gas barrier laminate, characterized in that the static friction coefficient between a surface of a functional layer opposite to a substrate side and a surface of a gas barrier layer opposite to the substrate side is 0.35 to 0.
80.
2. 2. The long gas barrier laminate according to claim 1, wherein the surface of the gas barrier layer opposite the substrate has an arithmetic mean roughness (Ra) of 5 nm or less and a maximum cross-sectional height (Rt) of a roughness curve of 100 nm or less.
3. 2. The long gas barrier laminate according to claim 1, wherein the functional layer is a hard coat layer made of a cured product of an active energy ray-curable resin composition.
4. 2. The long gas barrier laminate according to claim 1, wherein the smoothing layer is made of a cured product of an active energy ray-curable resin composition.
5. 2. The long gas barrier laminate according to claim 1, wherein the gas barrier layer is a layer obtained by modifying a layer containing a polysilazane compound.
6. A method for producing a long gas barrier laminate, comprising: a functional layer laminated on one surface of a substrate; and a smoothing layer and a gas barrier layer laminated in this order on the other surface of the substrate, comprising: A step (a-I) of forming a smoothing layer on a resin film for a substrate while transporting the resin film in a certain direction, and then winding up the obtained resin film with the smoothing layer into a roll; a step (a-II) of continuously unwinding the smoothing layer-attached resin film from the roll of the smoothing layer-attached resin film obtained in step (a-I) and transporting the smoothing layer-attached resin film in a constant direction, and forming a functional layer on the surface of the smoothing layer-attached resin film opposite the smoothing layer from an active energy ray-curable resin composition containing fine particles, the functional layer having an arithmetic average roughness (Ra) of 5 to 14.7 nm and a maximum cross-sectional height (Rt) of a roughness curve of 100 to 1000 nm on the surface opposite the resin film, and then winding up the obtained functional layer and the smoothing layer-attached resin film into a roll; and a step (a-III) of continuously unwinding the resin film with the functional layer and the smoothing layer obtained in step (a-II) from the roll of the resin film with the functional layer and the smoothing layer and transporting the resin film in a constant direction while forming a gas barrier layer having a static friction coefficient with the functional layer of 0.35 to 0.80 on the surface of the smoothing layer of the resin film with the functional layer and the smoothing layer, and then winding up the resulting gas barrier laminate into a roll; The method for producing a long gas barrier laminate, comprising the steps of:
7. A method for producing a long gas barrier laminate, comprising: a functional layer laminated on one surface of a substrate; and a smoothing layer and a gas barrier layer laminated in this order on the other surface of the substrate, comprising: a step (b-I) of forming a functional layer on a surface of the resin film opposite to the resin film, the functional layer having an arithmetic average roughness (Ra) of 5 to 14.7 nm and a maximum cross-sectional height (Rt) of a roughness curve of 100 to 1000 nm, using an active energy ray-curable resin composition containing fine particles, while conveying the resin film for the substrate in a fixed direction, and then winding up the obtained resin film with the functional layer into a roll; a step (b-II) of continuously unwinding the functional layer-attached resin film from the roll of the functional layer-attached resin film obtained in step (b-I) and transporting the functional layer-attached resin film in a constant direction while forming a smoothing layer on the surface of the functional layer-attached resin film opposite the functional layer, and then winding up the resulting functional layer and smoothing layer-attached resin film into a roll; and a step (b-III) of continuously unwinding the resin film with a functional layer and a smoothing layer from the roll-like resin film with a functional layer and a smoothing layer obtained in step (b-II) and transporting the resin film in a constant direction while forming a gas barrier layer having a static friction coefficient with the functional layer of 0.35 to 0.80 on the surface of the smoothing layer of the resin film with a functional layer and a smoothing layer, and then winding up the resulting gas barrier laminate into a roll; The method for producing a long gas barrier laminate, comprising the steps of:
8. A method for producing a long gas barrier laminate described in claim 6 or 7, wherein the static friction coefficient between the functional layer surface and the smoothing layer surface of the resin film with the functional layer and smoothing layer is 0.35 to 0.
80.
9. A method for manufacturing a long gas barrier laminate as described in claim 6 or 7, wherein the arithmetic mean roughness (Ra) of the smoothing layer surface of the resin film with the functional layer and smoothing layer is 5 nm or less, and the maximum cross-sectional height (Rt) of the roughness curve is 100 nm or less.
Citation Information
Patent Citations
Transparent gas-barrier film, transparent conductive electrode base material, display element, solar cell, or face-shaped emitter using the film
JP2003154596A
Surface-roughened optical film, method for producing the same, polarizing plate and image display device
JP2007052333A
Hard coat film and its manufacturing method
JP2009029126A
Resin film, process for producing the resin film, and organic electroluminescent element
WO2010026852A1
Gas barrier laminate, method for producing same, member for electronic devices, and electronic device
WO2013147090A1